2006
DOI: 10.5194/angeo-24-2333-2006
|View full text |Cite
|
Sign up to set email alerts
|

Probing of medium-scale traveling ionospheric disturbances using HF-induced scatter targets

Abstract: Abstract.Experimental results from the Tromsø and Sura heating experiments at high and mid-latitudes are examined. It is shown that the combination of HF-induced target and bi-static HF Doppler radio scatter observations is a profitable method for probing medium-scale traveling ionospheric disturbances (TIDs) at high and mid-latitudes. HF ionospheric modification experiments provide a way of producing the HF-induced scatter target in a controlled manner at altitudes where the sensitivity to TIDs is highest. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…Djuth et al (1985) found from VHF radar observations during Tromsø HF heating experiments, that the generation of striations in the auroral E-region was possible when the heater frequency, f H , exceeded the critical frequency foEs by 0.2 MHz. The same result was obtained by Blagoveshchenskaya et al (1999Blagoveshchenskaya et al ( , 2006a when strong heaterinduced striations were observed in the auroral E-region with bi-static HF radio scatter. Striations have also been observed from Tromsø HF heating experiments in the night-side Fregion of the auroral ionosphere when foF2 drops below the heater frequency by up to 0.5 MHz (Blagoveshchenskaya et al, 2006b).…”
Section: Introductionsupporting
confidence: 73%
“…Djuth et al (1985) found from VHF radar observations during Tromsø HF heating experiments, that the generation of striations in the auroral E-region was possible when the heater frequency, f H , exceeded the critical frequency foEs by 0.2 MHz. The same result was obtained by Blagoveshchenskaya et al (1999Blagoveshchenskaya et al ( , 2006a when strong heaterinduced striations were observed in the auroral E-region with bi-static HF radio scatter. Striations have also been observed from Tromsø HF heating experiments in the night-side Fregion of the auroral ionosphere when foF2 drops below the heater frequency by up to 0.5 MHz (Blagoveshchenskaya et al, 2006b).…”
Section: Introductionsupporting
confidence: 73%
“…In thin semi-transparent E s layers typical of the midlatitude ionosphere, small-scale irregularities were not excited. In the experiments performed with the heating facility in Tromsø, the occurrence of AFAIs in the auroral E region was also observed in the night hours during reflection of a high-power HF O-mode wave from a thick sporadic E s layer when the methods of aspect and backward scattering [28][29][30] were employed.…”
Section: Excitation Of Small-scale Field-aligned Artificial In the Spmentioning
confidence: 91%
“…remains open. In the experiments using the heating facility in Tromsø, the AFAIs were also generated for f h > f 0F 2 (or f 0Es ) both in the nighttime auroral ionospheric F region [14] and in the sporadic E s layer [28,30]. Observations of stimulated luminescence of the perturbed region in the red (wavelength 630 nm) and green (557.7 nm) lines on the HAARP facility [31] show that the luminescence did not decay when the critical frequency was lower than the heater frequency.…”
Section: Some Features Of the Stimulated Electromagnetic Emission Of mentioning
confidence: 99%
“…When carrying out experiments with use for diagnostics of a method of aspect scattering [4,7] frequency shifts of the diagnostic transmitter of the same order, as well as recorded by us were received. In general, they correspond to the data obtained by us in these observations and in work [2].…”
Section: Results Of Investigation and Discussionmentioning
confidence: 99%